The Effect of Using a Spinal Orthosis on Non-Specific Lower Back Pain: Literature review - Suprayogi, Dody; Zubaidi, Alfan; Rahayu, Listianingrum Budi (Journal of Prosthetics Orthotics and Science Technology, 2025)
Background: Over time, various problems have emerged alongside societal developments, including those in the health sector. One common issue is musculoskeletal disorders, particularly low back pain (LBP). Nonspecific Low Back Pain (NSLBP) refers to a pain syndrome in the lower back region without a clearly identifiable cause. Spinal orthosis has been proposed as a potential treatment for back pain. Aims: This study aims to examine the effectiveness of spinal orthosis in managing low back pain through a literature review. Methods and Subjects: A literature review was conducted using databases such as Google Scholar, PubMed, and ScienceDirect. The keywords used included "spinal orthosis," "lumbar corset," and "low back pain." Only full-text English articles with an experimental design were included. Article selection followed the PRISMA diagram guidelines. Results: Low back pain can affect individuals of all ages, including adolescents and adults. Pain assessment tools such as the Visual Analog Scale (VAS) and Numeric Rating Scale (NRS) were commonly used in the studies. Among the types of spinal orthoses, Lumbosacral Orthosis (LSO) was found to be effective in reducing pain in individuals with low back pain. Conclusion: The use of a spinal orthosis, particularly a lumbosacral orthosis, in daily activities contributes to pain reduction in individuals suffering from nonspecific low back pain.